The Actualization of the Concept of National Fiqh in Building Religious Moderation in Indonesia - Arbanur Rasyid; Muhammad Basyrul Muvid; Maulana Arafat Lubis; Puji Kurniawan (Millah: Journal of Religious Studies, 2022)
This study intends to critically examine and analyze the process of national fiqh actualization in shaping an attitude of religious moderation. Bearing in mind, the problem of unity amidst differences is primary, so it must remain a serious concern to maintain the country’s resilience. The research method was qualitative with a library research approach, which collected a variety of relevant literature according to the topic of study. This study concludes that the concept of national fiqh has an orientation to unity and integrity in maintaining national sovereignty wrapped with nationalism. National fiqh’s relevance and religious moderation become a mutually reinforcing synergy because national fiqh seeks to build a nationalist humanistic paradigm to reduce differences. Then, the actualization of national fiqh in building Indonesia’s religious moderation is the appreciation of the teachings of Islam in a complex and contextualist manner, not merely normative or dogmatic, strengthened by the process of cultivating moderate, fair, tolerant, humanist, ethical, religious, and nationalist attitudes.